2015
DOI: 10.1016/j.cell.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Co-translational RNA Decay Reveals Ribosome Dynamics

Abstract: Summary It is generally assumed that mRNAs undergoing translation are protected from decay. Here we show that mRNAs are in fact co-translationally degraded. This is a widespread and conserved process affecting most genes, where 5’-3’ transcript degradation follows the last translating ribosome, producing an in vivo ribosomal footprint. By sequencing the ends of 5’phosphorylated mRNA degradation intermediates, we obtain a genome-wide drug-free measurement of ribosome dynamics. We identify general translation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
377
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(434 citation statements)
references
References 50 publications
(92 reference statements)
52
377
3
2
Order By: Relevance
“…However, a recent genome-wide survey of monophosphorylated 59 RNA ends in yeast showed that XRN1 is also involved in the accumulation of 59-truncated RNA ends protected by ribosomes during RNA decay (Pelechano et al, 2015). Using the plant degradome data, we identified an array of 59-truncated RNA ends separated at 30-nucleotide intervals in uORFs and CDSs, implying an array of stacked ribosomes (Figures 2 and 4 to 6).…”
Section: Comparison Of Ribosome Footprints In Rna Degradome Data Andmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent genome-wide survey of monophosphorylated 59 RNA ends in yeast showed that XRN1 is also involved in the accumulation of 59-truncated RNA ends protected by ribosomes during RNA decay (Pelechano et al, 2015). Using the plant degradome data, we identified an array of 59-truncated RNA ends separated at 30-nucleotide intervals in uORFs and CDSs, implying an array of stacked ribosomes (Figures 2 and 4 to 6).…”
Section: Comparison Of Ribosome Footprints In Rna Degradome Data Andmentioning
confidence: 99%
“…Pelechano et al (2015) also demonstrated that yeast 5Pseq data contain in vivo ribosome footprints, the products of cotranslation mRNA decay. The change in these ribosomeprotected termini captured by 5Pseq could reflect ribosome dynamics without the problems caused by translational inhibitors sometimes used in the generation of in vitro ribosome footprints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence diverse cellular stress conditions can rapidly perturb global and mRNAspecific protein synthesis via multiple mechanisms to achieve stress-specific translational reprogramming. In addition to revealing translation changes under stress conditions, ribosomal profiling techniques have provided mechanistic insights into elongation through the use of distinct inhibitors (Lareau et al 2014) as well as by identifying specific pauses during elongation (Pelechano et al 2015).…”
Section: Global Approaches To Studying Translation Controlsmentioning
confidence: 99%
“…Moreover, the mechanisms of translational reprogramming are stress specific. For example, the global response to amino acid starvation is dependent on Gcn2 and eIF2a phosphorylation, while the response to hydrogen peroxide involves inhibiting both initiation via Gcn2 and translation elongation (Shenton et al 2006), causing pausing at aspartic acid and serine codons according to ribo-seq experiments (Pelechano et al 2015); however, antioxidant-response mRNAs become well translated (Shenton et al 2006;Kershaw et al 2015). The response to glucose depletion is rapid and does not require eIF2a phosphorylation, with almost all ribosomes being lost from mRNAs within 1-2 min (Ashe et al 2000), perhaps via alterations in eIF4A function (Castelli et al 2011).…”
Section: Global Approaches To Studying Translation Controlsmentioning
confidence: 99%